Modelo costo, volumen, utilidad para la panificadora “Yguazú” ubicada en la provincia de Cotopaxi, cantón Latacunga, parroquia la Matriz, durante el segundo trimestre del 2022. - Mejía Rubio, Jenny Mariela (2023)
The present integrative project was advanced in the bakery “Yguazú” dedicated to the production and commercialization of bakery products, the main problem arises in the determination of the production costs because they stablish the sale price in an empirical way, in addition to not having an adequate control over them. The aim is to implement a cost-volume profit model to determinate the cost elements involved in production, in order to provide a sustainable tool for the bakery, focusing on decision making for the growth and development of the bakery. The type of research applied presents a quantitative approach, because techniques such as interviews and observation sheets were put in application, through which important information was found that permitted us to identify how the bakery works. The cost-volume-profit model carried out using Excel software allows us to know the fixed costs, variable costs, production costs, break -even point, contribution margin and changes in the variables. As a conclusion, it is established that through the model it was possible to detect that the flagship product is the snacks called llorón (weeping) because it has a daily production of 400 units and provides with an operational margin of 68% and a break-even point of 257 units, it was also possible to identify each of the elements involved in obtaining the cost of production and the break-even point of the products, this benefits the entity to take corrective actions.